External facilitators' perceptions of internal facilitation skills during implementation of collaborative care for mental health teams: a qualitative analysis informed by the i-PARIHS framework - Samantha L. Connolly; Jennifer L. Sullivan; Mona J. Ritchie; Bo Kim; Christopher J. Miller; Mark S. Bauer (BMC, 2020)
Abstract Background Facilitation is a key strategy that may contribute to successful implementation of healthcare innovations. In blended facilitation, external facilitators (EFs) guide and support internal facilitators (IFs) in directing implementation processes. Developers of the i-PARIHS framework propose that successful facilitation requires project management, team/process, and influencing/negotiating skills. It is unclear what IF skills are most important in real-world settings, which could inform recruitment and training efforts. As prior qualitative studies of IF skills have only interviewed IFs, the perspectives of their EF partners are needed. Furthermore, little is known regarding the distribution of implementation tasks between IFs and EFs, which could impact sustainability once external support is removed. In the context of an implementation trial, we therefore: 1) evaluated IFs' use of i-PARIHS facilitation skills, from EFs' perspectives; 2) identified attributes of IFs not encompassed within the i-PARIHS skills; and 3) investigated the relative contributions of IFs and EFs during facilitation. Methods Analyses were conducted within a hybrid type II trial utilizing blended facilitation to implement the collaborative chronic care model within mental health teams of nine VA medical centers. Each site committed one team and an IF to weekly process design meetings and additional implementation activities over 12 months. Three EFs worked with three sites each. Following study completion, the EFs completed semi-structured qualitative interviews reflecting on the facilitation process, informed by the i-PARIHS facilitation skill areas. Interviews were analyzed via directed content analysis. Results EFs emphasized the importance of IFs having strong project management, team/process, and influencing/negotiating skills. Prior experience in these areas and a mental health background were also benefits. Personal characteristics (e.g., flexible, assertive) were described as critical, particularly when faced with conflict. EFs discussed the importance of clear delineation of EF/IF roles, and the need to shift facilitation responsibilities to IFs. Conclusions Key IF skills, according to EFs, are aligned with i-PARIHS recommendations, but IFs' personal characteristics were also emphasized as important factors. Findings highlight traits to consider when selecting IFs and potential training areas (e.g., conflict management). EFs and IFs must determine an appropriate distribution of facilitation tasks to ensure long-term sustainability of practices. Trial registration Clinicaltrials.gov, September 7, 2015, #NCT02543840.